Nomenclatural notes of Salix wangiana and S. zangica var. tibetica (Salicaceae) - He, Li; Liao, Shuai; Chen, Shi-Pin; Zhang, Zhi-Xiang (Phytotaxa, 2016)
Working within the framework of the Flora of the Pan-Himalayas project, we examined many reports regarding Salix and found that the valid publication date for Salix wangiana is later than that for S. rhododendroides. Consequently, S. wangiana is treated as a synonym of S. rhododendroides instead of the reverse. Salix wangiana var. tibetica is invalid, and therefore the intended combination S. zangica var. tibetica indeed represents a new variety, for which the authorship is “C. Wang & C.F. Fang ex N. Chao”. Furthermore, the names S. rhododendroides and S. zangica var. tibetica are lectotypified.